Solusi Peningkatan Daya Beli Masyarakat Akibat Anjloknya Harga Rumput Laut - Regita Fatikah Sari; Henny Ritha; Reny Fitriana Kaban (CV. Kalimasada Group, 2025)
This research aims to describe the specifics of the problem of the lack of purchasing power of people in Lumintu food stalls due to the drop in seaweed prices in Nunukan Regency. North Kalimantan Province. The research method used is descriptive qualitative by interviewing several sources in the field according to current realities and related problems. The word is then researched thoroughly. The results of this research show that the drop in seaweed prices has had a big impact on the economy of the people in Nunukan Regency who only rely on their livelihood as seaweed farmers and thus has an impact on the lack of purchasing power of consumers in food stalls in Nunukan Regency, one of which is food stalls. . Lumintu. The author suggests a system of delaying selling and processing seaweed into ready-to-eat food to overcome the problem of reducing people's purchasing power for food at Lumintu stalls.